The Euphoric Sensations of Cigarettes: Exploring How Operant Conditioning May Be the Missing Link in the Theoretical Understanding of Antidrug Policies. (July 2018) - Borkowski, Elizabeth L.; Leal, Wanda E.
This study aims to examine how positive and negative reinforcers during an individual's first few cigarettes (cigarette initiation experiences) are associated with adulthood smoking behavior. Respondents from the Add Health were asked about subjective feelings during their first few cigarettes. Using ordinary least squares (OLS) and logistic regression, we examine the differential effects of positive and negative cigarette initiation experiences on 30-day cigarette use in adulthood and lifetime nicotine dependence. The results indicate that all measures of positive cigarette initiation experiences are positively associated with both cigarette measures; however, the opposite is not true of negative cigarette initiation experiences. The results highlight the misconceptions of antidrug policies aimed at punishment of users, by indicating that positive experiences influence later cigarette use more than negative experiences. These findings suggest that drug policies and initiatives aimed at punishment may be misguided and could benefit from adopting operant conditioning concepts that emphasize reinforcements.